Subtyping of Pathological Gamblers (PGs) : a review of the pathways model. - Lee, Ying Min. (2013)
The literature supports the presence of subtypes of pathological gamblers (PGs), each associated with distinct characteristics, risk factors, and etiological pathways to addiction. Although many models have been proposed for the subtyping of PGs, the literature is scattered, with individual studies focusing on a narrow range of criteria for classification. The current review attempts to provide an overarching framework that consolidates previous research by highlighting consistencies and similarities between the different models. Overall, the studies reviewed converge and support Blaszczynski and Nower’s (2002) three subtypes: behaviourally conditioned, emotionally vulnerable, and antisocial impulsivist gamblers. Furthermore, studies investigating individual risk factors confirm that different characteristics are selectively associated with different subtypes of PGs.